Телефон: [стихи] / Корней Чуковский ; худ. О. Ю. Горбушин - Чуковский Корней Иванович (Любимые книги детства, 2007)
Экземпляры: ф.14 (2008) / Инвентарный номер: 52433 / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: Ч-88 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-5